The effect of sand grain size and water on the green compression strength for greensand casting mould mixture - A.Azhar,; H.H.Hazril,; M.Redzuan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The focus of this research is to investigate the effect of water content and sand grain size on the green compression strength of a greensand casting mould mixture. Grain size is a major determinant of mould and core green compression strength and surface finish of the greensand casting product. Water influences the efficiency of binder which is bentonite clay in bonding the sand grain particles thus improving the green compression strength. The objective of this study is to study the effect of grain size and water on the green compression strength. The specimen is prepared by mechanical size grading and graded into three sizes which are 425 μm, 300 μm and 150 μm. Experiments are carried out in accordance with American Foundrymen Society (AFS) guidelines. Three ramming blows of 6666 grammes with a Ridsdale-Dietert metric standard rammer compact cylindrical test pieces with dimensions of Ø50 mm×50 mm in height made from varied sand grain size–water ratios bound with 5% bentonite. The test pieces are tested for green compression strength with Ridsdale-Dietert Universal Sand Strength Machine. The sand grain size of 150 μm is found to have superiority in green compression strength compared to two other sizes, and 3% water content gives the maximum green compression strength for all three sand samples sizes.